Talent management practices perceived by academicians in selected public higher learning institutions - Lukman@Zawawi, Mohamad; Kamal, M.Y. (2017)
Talent Management(TM) has been implemented in Public Higher Learning Institutions (PHLIs) in Malaysia for quite sometimes. However, the differences of TM system have made some PHLIs moving forward as compared to others in developing and creating human capital. Therefore, this research has been conducted to seek for further clarification on the significance difference of three selected PHLIs which are Universiti Sains Malaysia (USM), Universiti Pendidikan Sultan Idris (UPSI) and Universiti Teknologi Mara (UiTM). The quantitative method has been chosen as a primary data for this research and the descriptive survey has been conducted towards 714 respondents. Further, the data collected was analysed by using IBM Statistical Packages Social Sciences (SPSS). As a result, the significant differences of TM perceived by academicians revealed that there were significant differences existed whereby USM showed most significant practices in TM perceived by academicians as compared to other two PHLIs. As a conclusion, each PHLI have come up with their own strategies to attract, recruit, develop and retain their own talent in order to help the organization to grow excellent.